NEW STAGES AND PRACTICAL CONDITIONS FOR CREATING NATIONAL TEXTBOOKS AND ALPHABET BOOKS (Conferencea, 2023)
In this article, new stages and practical conditions for creating national textbooks and alphabet books. scientific-theoretical analysis.